Revision of the rare Buprestis subgenus Akiyamaia Kurosawa, 1988 (Coleoptera: Buprestidae: Buprestinae), with description of two new species - Qi, Zhi-Hao; Su, Rong-Xiang; Liao, Zhi-Yu; Ai, Hong-Mu; Ding, Bi; Song, Hai-Tian (Zootaxa, 2024)
In this paper, two new species of Buprestis subgenus Akiyamaia Kurosawa, 1988 are described: B. (A.) gengmini Qi & Song, new species from Yunnan Province, China and B. (A.) wenii Qi & Song, new species from Yen Bai Province, Vietnam. The descriptions and illustrations of two new species are provided, and the diagnostic characters are provided to distinguish the two new species from other related species. A key is given for identification of all Akiyamaia species.The holotype of B. (A.) costipennis (Fairmaire, 1891) and pictures of living individuals are illustrated for the first time.